2022
DOI: 10.3889/oamjms.2022.10404
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal B Natriuretic Peptide as a Prognostic Marker in Sepsis Induced Myocardial Dysfunction

Abstract: BACKGROUND: Sepsis-induced myocardial dysfunction (SIMD) is an increasingly recognized form of transient cardiac dysfunction in sepsis patients. AIM: The aim of the study was to evaluation of N-terminal pro brain natriuretic peptide (NT-pro BNP) as a predictor of SIMD and poor outcome in patients with sepsis or septic shock. METHODS: Forty patients were enrolled and divided into: Group 1 with sepsis; Group 2 with septic shock. Each group was subdivided according to the presence or absence of cardiomyopathy. Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Moreover, the study highlighted the predictive value of NT-pro BNP in sepsis-induced myocardial dysfunction, further emphasizing the significance of NT-pro BNP as a predictor of adverse cardiac events [ 45 ]. Additionally, the research demonstrated the importance of NT-pro BNP levels in acute exacerbation of COPD patients, showing that elevated NT-pro BNP was associated with poor outcomes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study highlighted the predictive value of NT-pro BNP in sepsis-induced myocardial dysfunction, further emphasizing the significance of NT-pro BNP as a predictor of adverse cardiac events [ 45 ]. Additionally, the research demonstrated the importance of NT-pro BNP levels in acute exacerbation of COPD patients, showing that elevated NT-pro BNP was associated with poor outcomes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%